Indole Antitumor Agents in Nanotechnology Formulations: An Overview - Eleonora Russo; Carola Grondona; Chiara Brullo; Andrea Spallarossa; Carla Villa; Bruno Tasso (MDPI AG, 2023)
The indole heterocycle represents one of the most important scaffolds in medicinal chemistry and is shared among a number of drugs clinically used in different therapeutic areas. Due to its varied biological activities, high unique chemical properties and significant pharmacological behaviors, indole derivatives have drawn considerable interest in the last decade as antitumor agents active against different types of cancers. The research of novel antiproliferative drugs endowed with enhanced efficacy and reduced toxicity led to the approval by U.S. Food and Drug Administration of the indole-based anticancer agents Sunitinib, Nintedanib, Osimertinib, Panobinostat, Alectinib and Anlotinib. Additionally, new drug delivery systems have been developed to protect the active principle from degradation and to direct the drug to the specific site for clinical use, thus reducing its toxicity. In the present work is an updated review of the recently approved indole-based anti-cancer agents and the nanotechnology systems developed for their delivery.